Constructing multilayered membranes with layer-by-layer self-assembly technique based on graphene oxide for anhydrous proton exchange membranes. (5th January 2020) - Jia, Tingting; Shen, Si; Xiao, Libang; Jin, Jin; Zhao, Jing; Che, Quantong
Graphical abstract: Highlights: Multicomponent membranes were prepared with the layer by layer self-assembly technique. (PU/GO/PDDA/GO)200 membranes exhibit the methanol permeability of (3.66–12.5) × 10 −8 cm 2 /s. Maximum proton conductivity is 1.83 × 10 −1 S/cm at 150 °C under anhydrous condition. Abstract: Layer-by-layer (LBL) self-assembly technique could nanoscopically construct the layered membranes and it has attracted more attention in the field of bionics, clean energy and microelectronics. The aim of this research to develop the multilayered membranes with the ordered deposition of components using LBL self-assembly technique. Successful preparation of anhydrous proton exchange membranes (PEMs) based on graphene oxide (GO) as polyanions, polyurethane (PU) and poly(diallyldimethylammonium chloride) (PDDA) as polycations have been demonstrated by identification of the ordered distribution of components and compact structure. While the prepared membranes were immersed into phosphoric acid (PA) solution, PA molecules were combined with the formation of PA doped membranes. In spite of PA dominating the proton conduction, the decreased proton conduction resistance is revealed from the lower activation energy owing to the multilayered structure. Specifically, the proton conductivity of 1.83 × 10 −1 S/cm at 150 °C was obtained for (PU/GO/PDDA/GO)200 /60%PA membranes. Moreover, the proton conductivity stability measurement demonstrated the component and mechanical stability, showing 1.47 × 10 −1 S/cm at 120 °C and 1.83 × 10 −1 S/cm at 140 °C. The result revealed that LBL self-assembly technique could provide a promising strategy to prepare multilayered membranes as membrane electrolytes using in high temperature proton exchange membrane fuel cells.